2002
DOI: 10.1074/jbc.m203924200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Iron Regulon Is Induced upon Cobalt Stress and Crucial for Cobalt Tolerance

Abstract: To identify yeast genes involved in cobalt detoxification, we performed RNA expression profiling experiments and followed changes in gene activity upon cobalt stress on a genome-wide scale. We found that cobalt stress specifically results in an immediate and dramatic induction of genes involved in iron uptake. This response is dependent on the Aft1 protein, a transcriptional factor known to regulate a set of genes involved in iron uptake and homeostasis (iron regulon). Like iron starvation, cobalt stress induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 43 publications
11
72
0
2
Order By: Relevance
“…In addition, the oxidative stress responsive genes, such as glutathione peroxidase, thioredoxin and glutaredoxin, were also induced (Table 3). Our results correlated well with a previous report on transcriptional response to cobalt (Stadler and Schweyen, 2002). The study also showed that cobalt stress induces the accumulation of iron in the yeast cells.…”
Section: Resultssupporting
confidence: 82%
“…In addition, the oxidative stress responsive genes, such as glutathione peroxidase, thioredoxin and glutaredoxin, were also induced (Table 3). Our results correlated well with a previous report on transcriptional response to cobalt (Stadler and Schweyen, 2002). The study also showed that cobalt stress induces the accumulation of iron in the yeast cells.…”
Section: Resultssupporting
confidence: 82%
“…8A). Deletion of AFT1 also abrogated the Co 2ϩ resistance in wild type and ⌬mrs3⌬mrs4 cells, confirming a recent report that Co 2ϩ resistance was due to the expression of Aft1p-regulated genes (21). Transformation of wild type cells with an AFT1-1 up allele results in increased expression of the CTR1-LacZ reporter construct (Fig.…”
Section: Changes In Copper Metabolismsupporting
confidence: 72%
“…cerevisiae is an ideal eukaryotic organism to study global gene expression in response to a variety of environmental variations including oxidative stress, heavy metal ions and heat shock. Previously, yeast transcriptome analysis under surplus cobalt stress revealed that the iron regulon participates in cobalt tolerance (Stadler and Schweyen, 2002). In contrast, we observed that surplus iron can serve as a growth stimulator to significantly accelerate the growth of yeast cells.…”
Section: Introductionmentioning
confidence: 58%